Structure of the Movement Forms of the Jaranan Art Dance at the Kridho Budoyo Studio, Jaya Bakti Village, Mesuji District, Ogan Komering Regency - Saputri, Eka Ani; Wardiah, Dessy; NAD, Nugroho (CV. Rayyan Dwi Bharata, 2023)
The background of this research is that the researcher wants to know the Structure of the Movement of the Jaranan Arts Dance in the Kridho Budoyo Studio, Jaya Bakti Village, Mesuji District, Ogan Komerin Ilir Regency. Mesuji District, Ogan Komering Ilir District. The purpose of this study was to find out how to describe the structure of the movements of the Jaranan Arts Dance at the Kridho Budoyo Studio, Jaya Bakti Village, Mesuji District, Ogan Komering Ilir Regency. The collection of research data is in the form of observations, interviews, and documentation from the head of the studio, dancers, and musicians. The structure of the movements of the Jaranan Art Dance at the Kridho Budoyo Studio, Jaya Bakti Village, Mesuji District, Ogan Komering Ilir Regency, there are 6 types of movements, namely Budalan Movement, Rete-reto Sabetan, Regular Sabetan, Ngecek, Worship, and Bambangan. Based on the research results that have been obtained that the Jaranan kridho budoyo dance has an initial, middle and final movement structure